Selecting the Appropriate Oral Cancer Cell Line: Characteristic-Based Recommendations from a Systematic Review (Journal of Cancer Research Updates, 2025)
Introduction: Oral squamous cell carcinoma (OSCC) research often relies on in vitro models to study tumor behaviour and evaluate therapeutic agents. However, variability in cell line characteristics and limited guidance on their selection pose challenges to research consistency and translational accuracy.Objective: To provide a comprehensive evaluation of OSCC cell lines based on anatomical origin/site, biological features and associated risk factors, offering evidence-based recommendations for their appropriate use.Method: A systematic review was conducted in PubMed database covering the period 1972 to 2024 using the keywords “human,” “oral squamous cell carcinoma,” and “cell line.” Inclusion criteria were English full-text publications describing human-derived OSCC cell lines. Cell lines of animal origin or with known contamination were excluded from this study.Results: Out of 524 records, 106 publications were analyzed. Japan and the USA led in cell line development. Most cell lines originated from male patients and the tongue was the predominant anatomical site for OSCC. Highly cited lines such as HSC-3, CAL-27, and SAS were favored for studies on metastasis, immune markers, and drug testing. Cell lines were categorized based on single or multiple risk exposures, including tobacco, alcohol, betel quid, and HPV infection.Conclusion: This review provides an evidence-based framework for selecting OSCC cell lines by anatomical origin/site, molecular features, and documented etiologic exposures. Therefore, researchers should align cell-line selection with the relevant characteristic background and the specific experimental goal (e.g., metastasis, immune-marker, or drug testing), prioritizing well-characterized models when reproducibility and translational relevance are key.